Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep31169
|View full text |Cite
|
Sign up to set email alerts
|

Anti-photoaging properties of the phosphodiesterase 3 inhibitor cilostazol in ultraviolet B-irradiated hairless mice

Abstract: We investigated whether cilostazol, an activator of cyclic adenosine monophosphate (cAMP)-dependent intracellular signaling, could inhibit ultraviolet B (UVB) irradiation-induced photoaging in HR-1 hairless mice. Cilostazol decreased wrinkle formation and skin thickness in UVB-irradiated mice, as well as increased staining of collagen fibers and inhibition of reactive oxygen species (ROS) formation in the skin. Moreover, the proteolytic activities of gelatinase matrix metalloproteinase (MMP)-9 and collagenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…UV‐induced ROS plays an important role in activating melanogenesis mediated by the MAPK signaling pathway (H.N. Kim, Gil, Kim, Shin, & Choi, ). Our preliminary study has also demonstrated that ROS inhibitor NAC can antagonize UVB‐induced activation of MAPK signaling pathway in melanocytes (Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…UV‐induced ROS plays an important role in activating melanogenesis mediated by the MAPK signaling pathway (H.N. Kim, Gil, Kim, Shin, & Choi, ). Our preliminary study has also demonstrated that ROS inhibitor NAC can antagonize UVB‐induced activation of MAPK signaling pathway in melanocytes (Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a cAMP increase, triggered by the activation of a specific G-protein-coupled receptor (GPCR; an adenosine A2A receptor, upstream of Adcy), inhibits the MMP pathway, thus stimulating collagen production in human dermal fibroblasts [10]. Topical cilostazol (cAMP phosphodiesterase inhibitor) application protects against UVB-mediated MMP expression and subsequent photoaging, including wrinkle formation in the skin of hairless mice, through cAMP-dependent intracellular signaling [11].…”
Section: Introductionmentioning
confidence: 99%
“…To examine changes in the epithermal thickness and density of collagen fibers in the dermis in the dorsal skin, the tissue sections were stained with Masson's trichrome staining kit (Abcam, Cambridge, MA, USA), as described by Kim et al [44] The stained sections were prepared as permeant slides. Five sections per each animal were randomly selected to analyze epithermal thickness and the density of collagen fibers.…”
Section: Masson's Trichrome Stainingmentioning
confidence: 99%